Opportunities Surrounding the Use of Sargassum Biomass as Precursor of Biogas, Bioethanol, and Biodiesel Production - Orozco-González, Jorge Gabriel; Amador-Castro, Fernando; Gordillo-Sierra, Angela R.; García-Cayuela, Tomás; Alper, Hal S.; Carrillo-Nieves, Danay (Frontiers in Marine Science, 2022)
Climate change (along with other factors) has caused an increase in the proliferation of brown algal mats floating freely along the Atlantic Ocean since 2011. These brown algae mats are composed of sea plants from the Sargassum genus. The gargantuan agglomeration of biomass flows alongside currents and lands in beaches belonging to the Eastern coasts of the Mexican Caribbean and several other countries in the region. These events, dubbed golden tides, harm the local economy and environment. Current elimination approaches involve the mechanical harvesting of the Sargassum and ultimate landfill disposal. However, explorations into the commercial application of other brown algae have elucidated the potential of Sargassum as a feedstock for valorization. This review informs the trends, challenges, and opportunities presented by the coastal invasion of this biomass. Primarily, the potential use of this material is as a precursor in biorefineries where multiple value-added products are generated concurrent with the ultimate production of biofuels.